2015
DOI: 10.1248/bpb.b15-00356
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1α,25-Dihydroxyvitamin D<sub>3</sub> on Intestinal Absorption and Disposition of Adefovir Dipivoxil and Its Metabolite, Adefovir, in Rats

Abstract: The aim of this study was to investigate the effect of 1α,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ), an active form of vitamin D, on the oral absorption and disposition of adefovir dipivoxil (P-glycoprotein (P-gp) substrate) and its major active metabolite, adefovir (multidrug resistance-associated protein 4 (Mrp4) substrate), in rats. The pharmacokinetics of intravenous adefovir and oral adefovir dipivoxil was evaluated in control and 1,25(OH) 2 D 3 -treated rats. The intestinal absorption of adefovir dipivox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The 1,25(OH) 2 D 3 solution was then diluted to 2.56 nmol/mL with a vehicle (filtered corn oil). Rats ( n = 5 in each group) were administered an intraperitoneal injection at a dose of 0 (vehicle) or 2.56 nmol/kg, daily for 4 consecutive days, as reported previously (Chow et al, , ; Kim et al, ; Maeng, Durk, Chow, Ghoneim, & Pang, ; Yoon et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1,25(OH) 2 D 3 solution was then diluted to 2.56 nmol/mL with a vehicle (filtered corn oil). Rats ( n = 5 in each group) were administered an intraperitoneal injection at a dose of 0 (vehicle) or 2.56 nmol/kg, daily for 4 consecutive days, as reported previously (Chow et al, , ; Kim et al, ; Maeng, Durk, Chow, Ghoneim, & Pang, ; Yoon et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we investigated the effect of 1,25(OH) 2 D 3 on the oral absorption and disposition of adefovir dipivoxil (a P‐gp substrate) and its major active metabolite, adefovir (an MRP4 substrate), in rats. The previous study first demonstrated that 1,25(OH) 2 D 3 treatment enhanced the oral absorption of adefovir dipivoxil and increased the systemic exposure of adefovir in vivo, likely via the induction of basolateral MRP4 expression in rat intestine (Yoon, Son, Kim, Choi, & Maeng, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the mRNA/protein expressions and activities of multidrug resistance-associated protein 4 (MRP4), P-glycoprotein (P-gp), cytochrome P450 3A4 (CYP3A4), and multidrug resistance-associated protein 2 (MRP2) in Caco-2 cells were increased by 1,25(OH) 2 D 3 treatment in vitro [9,10]. In terms of transporter-mediated drug-drug interactions (DDIs), 1,25(OH) 2 D 3 significantly reduced the renal clearances of cefdinir and cefadroxil by down-regulating organic anion transporter 1 (OAT1) and organic anion transporter 3 (OAT3) expressions in rat kidney [11], but enhanced the oral absorption of adefovir dipivoxil by inducing MRP4 in rat intestine [12]. In the mice treated with 1,25(OH) 2 D 3, the pharmacokinetics of digoxin, a P-gp probe drug, was significantly affected in vivo, resulting in increased total clearance and renal clearance via regulation of P-gp by VDR activation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CdG, as well as ETV, is thought to be absorbed in the upper small intestine, with the result that it is rapidly absorbed after oral administration. It should also be noted that when orally administered, CdG shows a good bioavailability (approximately 70% in rats) similar to other NAs (ETV: approximately 78% in rats, adefovir dipivoxil: approximately 50% in rats). These findings indicate that CdG has the necessary properties for use as an oral preparation, similar to other NAs for HBV treatment.…”
Section: Discussionmentioning
confidence: 93%